Muscle composition in relation to age and sex - Forsberg, A. M.; Nilsson, E.; Werneman, J.; Bergström, J.; Hultman, E. (CLINICAL SCIENCE, 1991)
1. A method is described enabling the determination of fat, water, electrolytes, protein, DNA, RNA and total creatine in a single sample of human muscle obtained by the percutaneous needle-biopsy technique. The amino acid content can also be analysed in the same muscle sample. 2. Fifty healthy subjects were studied: 29 between 19 and 40 years of age, 11 between 41 and 60 years of age, and 10 between 61 and 85 years of age. The two groups aged less than 60 years showed only marginal differences in muscle composition, whereas the highest age group showed increases in muscle fat content in relation to tissue weight and decreases in alkali-soluble protein content in relation to both tissue weight and tissue DNA content. Also, potassium, magnesium, total creatine and RNA contents were decreased in this age group when related to tissue DNA content. When alkali-soluble protein was used as a reference base, only magnesium content was decreased. 3. A comparison was also made between female (n = 23) and male (n = 18) subjects in the age groups below 60 years. Differences observed included a higher fat content in female muscle, and an increase in total creatine content in relation to tissue weight. The alkali-soluble protein content was lower per muscle cell in the females when calculated on the basis of DNA content. 4. The results show that in the assessment of muscle constituents, age and sex must be taken into account.